Synchronous Malignant Gastrointestinal Neuroectodermal Tumor and SMARCA4-Deficient Undifferentiated Carcinoma With Independent Origins in the Small Intestine: A Case Report - Chen, Cuimin; Yin, Weihua; Wang, Xingen; Li, Ping; Chen, Yaoli; Jin, Xianglan; Yang, Ping; Wu, Huanwen (Frontiers in Oncology, 2021)
Background Malignant gastrointestinal neuroectodermal tumor (GNET) is a rare malignant mesenchymal neoplasm that commonly arises in the small bowel, stomach or colon. Meanwhile, SMARCA4-deficient undifferentiated carcinoma is a rarely reported entity with highly aggressive behavior that may involve the ovary, lung, gastrointestinal (GI) tract, endometrium and other organs. To our knowledge, we describe for the first time, an extremely rare case of synchronous GNET and SMARCA4-deficient undifferentiated carcinoma with independent origins in the small intestine. Case Presentation A 46-year-old woman presented with multiple small intestine masses and underwent surgical resection. Two distinct entities, GNET and SMARCA4-deficient undifferentiated carcinoma, were identified. GNET was composed of epithelioid and spindle cells with clear or eosinophilic cytoplasm arranged in sheets, nest, papillary, fascicular, palisade, rosette like or pseudoalveolar pattern. The neoplastic cells were positive for S-100 and SOX-10. Ewing sarcoma breakpoint region 1 gene (EWSR1) rearrangement was confirmed by fluorescence in situ hybridization (FISH), and EWSR1-CREB1 fusion was revealed by next-generation sequencing (NGS). SMARCA4-deficient undifferentiated carcinoma was composed mainly of poorly adhesive rhabdoid cells with eosinophilic cytoplasm arranged in a diffuse pattern. Multifocal necrosis, brisk mitotic figures as well as multinucleated tumor cells were observed. The neoplastic cells diffusely expressed pancytokeratin and vimentin, and was negative for SMARCA4(BRG1). Frame shift mutation of SMARCA4 was detected by NGS. Conclusions This is the first report that GNET and SMARCA4-deficient undifferentiated carcinoma occurred simultaneously in the small intestine, with the latter showing multiple involvement of the jejunum and ileum. The potential mechanism underlying co-existence of these two rare malignancies is unknown and need further investigations and concern.